The concise encyclopedia of applied linguistics - Chapelle, Carol A. (Wiley Blackwell, 2020)
"The Concise Encyclopedia of Applied Linguistics introduces readers to language-related issues that arise in the real world where languages are learned and used. It is a reference work compiled from the more extensive Encyclopedia of Applied Linguistics, which in 2019 was available in close to 1,000 libraries and professional organizations throughout over 50 countries worldwide.1 Usage data from the electronic versions of The Encyclopedia of Applied Linguistics were consulted to create The Concise Encyclopedia of Applied Linguistics by updating 180 of the most accessed entries from the Encyclopedia. The Concise Encyclopedia of Applied Linguistics was created to offer readers a vivid picture of the range of issues and research approaches in the diverse field of applied linguistics"--